Japanese Language Learning Media in Indonesia at the High School/SMK/equivalent Level Curriculum K13 and Merdeka - Erika Selphie Damayanti; Adhinda Zahro Haania; Katon Setyawan; Goldwag Megan (Lingeduca: Journal of Language and Education Studies, 2023)
The Japanese colonization of Indonesia, which lasted for three and a half years, had a profound impact on Indonesian history. With a time span not much longer than the Dutch colonization, the Japanese colonization had a major effect on Indonesia. It affected all aspects, including language. The interest in the Japanese language, and its inclusion in the Indonesian curriculum, cannot be separated from the history between Indonesia and Japan and the good bilateral relations between the two. The Japanese language as education is seen as a whole system that includes curriculum, materials, facilities, teacher-learners, teaching methodology, teaching media, and evaluation. This study aims to find out the Japanese language learning media in Indonesia at the Senior High School level and the equivalent to see how learning media can be done in learning a foreign language, namely Japanese. Data is collected using literature study techniques with descriptive-qualitative methods that describe data systematically and in detail to explore social phenomena or the real situation of Japanese language learning K13 Curriculum and Merdeka Curriculum at the SMA / SMK / equivalent level in the use of learning media. The results of the study state that mobile applications and device-based Japanese online dictionaries can be used for Japanese language learning at the SMA / SMK / equivalent level as basic or beginner level learners.